Comparison of hospital length of stay and hospitalization costs among patients with non-valvular atrial fibrillation treated with apixaban or warfarin: An early view. (2nd August 2016) - Xie, Lin; Vo, Lien; Keshishian, Allison; Price, Kwanza; Singh, Prianka; Mardekian, Jack; Bruno, Amanda; Baser, Onur; Kim, Jully; Tan, Wilson; Trocio, Jeffrey
Abstract: Objective: To quantify and compare hospital length of stay (LOS) and costs between hospitalized non-valvular atrial fibrillation (NVAF) patients treated with either apixaban or warfarin via a large claims database. Methods: Adult patients hospitalized with AF were selected from the Premier Perspective Claims Database (01JAN2013-31MARCH2014). Patients with evidence of valvular heart disease, valve replacement procedures, or pregnancy during the index hospitalization were excluded. Patients treated with apixaban or warfarin during hospitalization were identified. Propensity score matching (PSM) was performed to control for baseline imbalances between patients treated with apixaban or warfarin. Primary outcomes were hospital LOS (days), post-medication administration LOS, and index hospitalization costs, and were compared using paired t -tests in the matched sample. Results: Before PSM, 2894 apixaban and 124, 174 warfarin patients were identified. Patients treated with warfarin were older and sicker compared to those treated with apixaban. After applying PSM, a total of 2886 patients were included in each cohort, and baseline characteristics were balanced. The mean (standard deviation [SD] and median) hospital LOS was significantly ( p  = 0.002) shorter for patients treated with apixaban for 5.1 days (5.7 and 3) compared to warfarin for 5.5 days (4.8 and 4). The trend appeared consistent in the hospital LOS from point of apixaban or warfarin administration to discharge (4.5 vs 4.7 days, p  = 0.051). Patients administered apixaban incurred significantly lower hospitalization costs compared to those administered warfarin ($11, 262 vs $12, 883; p  < 0.001). Conclusions: Among NVAF patients, apixaban treatment was associated with significantly shorter hospital LOS and lower costs when compared to warfarin treatment.